The apple producers' choice between hail insurance and anti-hail nets. Issue 1 (25th June 2021) - Rogna, Marco; Schamel, Guenter; Weissensteiner, Alex
Abstract : Purpose: Hailstorms are a major risk in agriculture. In order to mitigate the negative consequences on farm revenues, in the present paper the authors analyse the choice between insurance contracts and anti-hail nets. Furthermore, the authors discuss the consequences of anti-hail nets adoption on the actuarial soundness of the insurance market. Design/methodology/approach: In this paper the authors firstly develop a theoretical model based on expected utility theory to compare the profitability of no-hedging against insurance and anti-hail nets. Subsequently, they test their theoretical model predictions with data of South Tyrolean apple producers. Findings: The authors find that the benefit of anti-hail nets compared to insurance is an increasing function of the overall risk of hail damages, of the farmers' level of risk aversion and of the worth of the agricultural output. Practical implications: Given the authors' findings that anti-hail nets are more profitable for riskier, risk-averse and high-profitable farmers, the diffusion of anti-hail nets could be beneficial for the actuarial soundness of insurance markets. Originality/value: The model developed in the paper is specifically designed to compare the profitability of different agricultural hedging options and can be easily extended to cover other hazards.